Modelling the impact of a healthy diet on cardiovascular disease and cancer mortality. Issue 5 (15th December 2010) - Scarborough, Peter; Nnoaham, Kelechi E; Clarke, Dushy; Capewell, Simon; Rayner, Mike
Abstract : Background: Quantifying the potential health benefits of improvements in the nutritional quality of the average diet of a population would provide evidence for resource allocation between population-level interventions aimed at reducing chronic disease. Methods: A model was built linking consumption of food components with biological risk factors (blood pressure, serum cholesterol and obesity) and subsequent mortality from coronary heart disease, stroke and cancer. Meta-analyses of individual-level studies that quantified the RR of increased consumption/increased risk factor level on disease outcomes were used to build the model. The sensitivity of the model to the results from the meta-analyses was assessed with Monte Carlo simulations. Country-specific estimates of current nutrient intake compared against dietary recommendations for the UK were used to demonstrate the model. Results: Approximately 33 000 deaths per year would be avoided if UK dietary recommendations were met. The modelled reduction in deaths for coronary heart disease was 20 800 (95% credible interval 17 845–24 069), for stroke 5876 (3856–7364) and for cancer 6481 (4487–8353). Over 15 000 of the avoided deaths would be due to increased consumption of fruit and vegetables. Conclusions: The developed model estimates the impact of population-level dietary changes and is robust. Achieving UK dietary recommendations for fruit and vegetable consumption (five portions a day) would result in substantial health benefits—equivalent benefits would be achieved if salt intakes were lowered to 3.5 g per day or saturated fat intakes were lowered to 3% of total energy.